2014
DOI: 10.7717/peerj.449
|View full text |Cite
|
Sign up to set email alerts
|

A third-generation dispersion and third-generation hydrogen bonding corrected PM6 method: PM6-D3H+

Abstract: We present new dispersion and hydrogen bond corrections to the PM6 method, PM6-D3H+, and its implementation in the GAMESS program. The method combines the DFT-D3 dispersion correction by Grimme et al. with a modified version of the H+ hydrogen bond correction by Korth. Overall, the interaction energy of PM6-D3H+ is very similar to PM6-DH2 and PM6-DH+, with RMSD and MAD values within 0.02 kcal/mol of one another. The main difference is that the geometry optimizations of 88 complexes result in 82, 6, 0, and 0 ge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 31 publications
0
46
0
1
Order By: Relevance
“…A general similarity between all SQM methods is parameterization, which, if conducted carefully, can minimize accuracy issues for special purpose applications. [30][31][32][33][34][35][36] Among the most frequently used Hartree-Fock based zero-differential overlap (ZDO) methods are PM6, [37][38][39][40][41][42] -used for the computation of ground state structures and energies [43][44][45][46] -and OM2, [47][48][49][50][51] which is extensively applied in excited state dynamics studies. [52][53][54][55][56] Over the past decades, density functional tight binding (DFTB) methods, [57][58][59][60][61][62][63][64][65][66] as derived from DFT, have found more attention, whereat in recent years the extended tightbinding (xTB) family of methods has been developed.…”
Section: Introductionmentioning
confidence: 99%
“…A general similarity between all SQM methods is parameterization, which, if conducted carefully, can minimize accuracy issues for special purpose applications. [30][31][32][33][34][35][36] Among the most frequently used Hartree-Fock based zero-differential overlap (ZDO) methods are PM6, [37][38][39][40][41][42] -used for the computation of ground state structures and energies [43][44][45][46] -and OM2, [47][48][49][50][51] which is extensively applied in excited state dynamics studies. [52][53][54][55][56] Over the past decades, density functional tight binding (DFTB) methods, [57][58][59][60][61][62][63][64][65][66] as derived from DFT, have found more attention, whereat in recent years the extended tightbinding (xTB) family of methods has been developed.…”
Section: Introductionmentioning
confidence: 99%
“…The structures are geometry optimized using PM6-D3H+ (Kromann et al, 2014) using the PCM solvation model (Tomasi et al, 2005;Steinmann et al, 2013) and the CHARMM22/CMAP force field (Mackerell, 2004) using the GB/SA solvation model (Qiu et al, 1997) with the 1UBQ (Vijay- Kumar et al, 1987) and 2OED (Ulmer et al, 2003) structures as starting points. The PM6-D3H+ optimizations are done using the GAMESS program (Schmidt et al, 1993) with a convergence criterion of 5 × 10 −4 atomic units, while the CHARMM22/CMAP optimizations are done using TINKER (Ponder and Richards, 1987) with the default convergence criterion of 0.01 kcal/mole/Å.…”
Section: Nmr Calculations and Protein Structures Usedmentioning
confidence: 99%
“…For these systems, the trans-chalcone 1 molecule was flipped on itself to adopt the three other available conformation in the groove with respect to the peroxide and the N-terminal (see figure 4A, B, C and D). The four supramolecular complexes were then energy minimized without constraints using the PM6-D3H+ method 25 implemented in the GAMESS software. 26 Analysis of the resulting supramolecular complexes showed that only the conformation depicted in figure 4A presented a reactive conformation with respect to the peroxide with a distance of 2.5A and angle of 98 degree close to the dunitz angle.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%